Pengaruh sedentary lifestyle terhadap kesehatan mental pada remaja - Tiara Ash Syafa; Misrah Misrah (SCHOULID: Indonesian Journal of School Counseling, 2024)
This research aims to analyze the influence of a sedentary lifestyle on mental health among teenagers in Sei Rotan village, Percut Sei Tuan subdistrict. This research uses a quantitative approach with descriptive methods to measure the influence of variables. Data was obtained through a Google Form questionnaire using the Accidental Sampling technique with a total of 60 respondents (aged 18-21 years) in their late teens. Data analysis includes univariate tests, bivariate analysis and bar charts. The results showed that of the total 60 respondents, there were 40 respondents who had a high sedentary lifestyle, 16 people (40.0%) experienced severe mental health disorders, then 23 people (57.5%) experienced moderate mental health disorders, and only 1 person (2.5%) experienced mental health problems. suffer from low mental health disorders. Meanwhile, of the total of 18 respondents with a moderate sedentary lifestyle, 2 people (11.1%) experienced high mental health disorders, 16 people (88.9%) experienced moderate mental health disorders, and none experienced low mental health disorders. Finally, of the 2 respondents with a low sedentary lifestyle, 2 people (100.0%) experienced low mental health disorders. It is concluded that the high incidence of mental health disorders in adolescents caused by a sedentary lifestyle can be a concern for all of us so that it does not cause more serious conditions in the future. This research not only provides insight into the relationship between a sedentary lifestyle and mental health in adolescents, but also provides a basis for practical actions and policies that can be used as a basis for local governments to formulate policies that support improving sports and recreation facilities in the village environment, so that teenagers have easier access to physical activities that can improve the welfare of teenagers in Sei Rotan Village.